Alcohol and cannabis consumption in patients with inflammatory bowel disease: prevalence, pattern of consumption and impact on the disease. Issue 1 (26th October 2022) - Martinho-Grueber, Maude; Kapoglou, Ioannis; Bravo, Francisco; Sarraj, Riad; Benz, Eileen; Restellini, Sophie; Biedermann, Luc; Rogler, Gerhard; Vavricka, Stephan R.; Schoepfer, Alain; Maillard, Michel H.; Michetti, Pierre; et al.
Abstract : Objectives of the study: There is little guidance regarding the impact of alcohol and cannabis on the clinical course of inflammatory bowel disease. The aim of this study was to assess the prevalence, sociodemographic characteristics and impact of alcohol and cannabis use on the clinical course of the disease. Methods: We performed an analysis of prospectively collected data within the Swiss Inflammatory Bowel Disease Cohort Study with yearly follow-ups and substance-specific questionnaires. We analyzed the prevalence of use, the profile of users at risk for addiction and the impact of alcohol and cannabis on the course of the disease. Results: We collected data of 2828 patients included between 2006 and 2018 and analyzed it according to their completion of specific surveys on alcohol and cannabis use. The prevalence of patient-reported active use was 41.3% for alcohol and 6% for cannabis. Heavy drinkers were over-represented among retired, married smokers receiving mostly aminosalicylates and less immunosuppression. In ulcerative colitis patients, low-to-moderate drinking was associated with less extensive disease. Cannabis users were often students with ileal Crohn's disease. Conclusion: A significant proportion of patients with inflammatory bowel disease consume alcohol or cannabis. Heavy alcohol consumption is most likely in male smokers >50 years, whereas young men with ileal disease rather use cannabis.